Uji Aktivitas Antibakteri Ekstrak Etanol Jantung Pisang Kepok (Musa x Paradisiaca L.) Terhadap Bakteri Staphylococcus Aureus - Laila Novia Safitri; Ade Maria Ulfa; Selvi Marcellia (Peneliti.net, 2023)
Gastrointestinal infection is an infection caused by several bacteria, including Staphylococcus aureus. The heart of Kepok Banana (Musa x paradisiaca L.) contains dietary fiber which can be used for human health, especially digestion. This study aims to determine the extract of the kepok banana flower contains antibacterial properties against Staphylococcus aureus bacteria using the ultrasonic method. Ultrasonic method, this method is an extraction method without heating, the extraction results obtained by the ultrasonic method were 17.58%, the results of the phytochemical screening of the kepok banana flower extract found the presence of alkaloids, flavonoids, tannins, saponins, and phenolics. The results showed that kepok banana flower extract had an inhibitory effect on the growth of Staphylococcus aureus bacteria with a diameter of 1.90 mm at a concentration of 24% which was included in the weak category. Antibacterial test results were analyzed using ANOVA. The results of the statistical analysis showed that there were significant differences in the inhibition zones, namely 0.000 (sig <0.005) between all concentrations. From this study it can be concluded that kepok banana flower extract (Musa x paradisiaca L.) has an inhibitory effect on Staphylococcus aureus bacteria in the weak category at all concentrations